Differences in oncological outcomes and inflammatory biomarkers between right‐sided and left‐sided stage I‐III colorectal adenocarcinoma. Issue 4 (21st November 2019) - Guo, Dongming; Li, Xinxin; Xie, Aosi; Cao, Qiangjian; Zhang, Jinhai; Zhang, Feiran; Li, Wei; Chen, Juntian
Abstract: Background: The aim of this study was to investigate the differences in oncological outcome and inflammatory biomarkers between right‐sided colon cancer (RCC) and left‐sided colorectal cancer (LCRC). Methods: We retrospectively analyzed 339 patients with stage I‐III colorectal cancer, including 125 RCC patients and 214 LCRC patients, who underwent radical resection from January 2012 to January 2014. Comparison of neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and lymphocyte‐to‐monocyte ratio (LMR) between RCC and LCRC was evaluated using the Mann‐Whitney U test. Overall survival (OS) and disease‐free survival (DFS) were analyzed using Kaplan‐Meier analysis and compared using the log‐rank test. Univariate and multivariate Cox regression analyses were used to identify the prognostic value of inflammatory markers. Results: Patients with RCC had higher NLR ( P = .002) and PLR ( P < .001) but lower LMR ( P = .002) compared to LCRC. In stage I‐III, RCC showed poorer OS and DFS than LCRC (61.6% vs 71.5%, P = .018; 64.8% vs 76.2%, P = .006). Univariate and multivariate analyses indicated that NLR, PLR, and LMR were independent predictors for both OS and DFS in RCC, whereas only PLR was found to be an independent prognostic predictor in LCRC. Conclusion: The prognosis and prognostic value of inflammatory biomarkers were significantly different between RCC and LCRC. Novel therapeutic strategies are needed, and proper prognostic predictors should be selected according to colorectal tumor location.